Preparation of Electrochemical Biosensor Systems for the Analysis of Biological Objects: a Reasonable Choice of Modifications of the Working Surface of Electrodes for Performing Research in the "Smart Electrode" Mode - Shumyantseva, V.V.; Agafonova, L.E.; Bulko, T.V.; Kuzikov, A.V.; Masamrekh, R.A. (Biomedical Chemistry: Research and Methods, 2020)
The electrochemical method of analysis of biological objects based on the reaction of electro-oxidation/electro-reduction of molecules is considered. Materials and complex systems for modifying electrodes as well as methods for producing modified electrodes to increase the sensitivity of recording the flow of electrochemical reactions on the surface of the electrodes are described. Methods of electrode modifications based on synthetic lipid-like didodecyldimethylammonium bromide, gold and silver nanoparticles, one-dimensional nanoparticles based on lead compounds, titan oxide nanoparticles, dispersions of carbon nanotubes in organic solvents, in polymers with different chemical structure are considered. It is shown that the appropriate functionalization of the working electrode surface makes it possible to increase the sensitivity of the electrochemical biosensor system and decrease the limit of detection. The results are presented in the form of an algorithm applicable for selection the beneficial type of modified electrode for the corresponding electrochemical reaction and biosample analysis.